Technical and anatomical factors affecting intra-arterial chemotherapy fluoroscopy time and radiation dose for intraocular retinoblastoma. (13th June 2019) - Area, Corey; Yen, Christopher J; Chevez-Barrios, Patricia; Herzog, Cynthia; Kan, Peter; Zheng, Wei; Lin, Frank; Chintagumpala, Murali; Gombos, Dan; Chen, Stephen R
Abstract : Background: Intra-arterial chemotherapy has an increasingly prominent role in the management of retinoblastoma. One concern regarding this technique is procedural radiation exposure. Objectives: To examine the effects of our institution's procedural technique on fluoroscopy parameters for patients undergoing intra-arterial chemotherapy infusions for intraocular retinoblastoma. Secondary goals included describing the effect of anatomical variations of the carotid siphon and ophthalmic artery on radiation dose. Methods: A retrospective review of pediatric patients with retinoblastoma referred to interventional neuroradiology for chemosurgery was performed. Techniques were classified as: A (1.2 Fr or 1.5 Fr microcatheter with continuous verapamil flush, advanced without guide through a 2 Fr sheath) or B (1.5 Fr or 1.7 Fr microcatheter advanced within a 4 Fr base catheter, through a 4 Fr sheath). Statistical analysis was performed to determine if there was a significant difference in fluoroscopy parameters based on technique or due to anatomical variation. Results: 26 patients were treated with 94 intra-arterial chemotherapy infusions. 34 procedures were performed using technique A and 60 using technique B. Mean fluoroscopy time (4.75 min), fluoroscopy dose (23.3 mGy), and dose–area product (DAP; 85.2 μGy.m 2 ) for technique A were significantly lower (p value <0.05) than for technique B, 14.0 min., 191 mGy, and 586 μGy.cm 2, respectively. Conclusions: Microcatheter-only technique with continuous verapamil infusion resulted in decreased fluoroscopy times, DAP, and radiation doses at our institution for the treatment of intraocular retinoblastoma. Furthermore, our fluoroscopy times using this technique are the lowest reported in the current literature. Additionally, our anatomical analysis has demonstrated a positive correlation between increasing vessel tortuosity and fluoroscopy times.